1D/3D Co(II)-based coordination polymers: protective effect on Alzheimer's disease by reducing Aβ accumulation and neurons apoptosis in mice. Issue 10 (10th August 2020) - Chen, Cong; Wang, Bu-Fei; Zeng, Chao-Sheng; Chen, Min; Chen, Lin; Su, Qing-Jie; Xing, Huai-Jie
Abstract: Two new mixed-ligand coordination polymers (CPs) with the chemical formulae of [Co(L)(phen)]n (1, phen = 1, 10-phenanthroline and [Co(L)(4, 4′-bipy)4 ·2H2 O]n (2, 4, 4′-bipy = 4, 4′-bipyridine) have been successfully synthesized by the solvothermal reaction of 1, 4-bis(3-carboxylbenzyl)piperazine acid (H2 L) and different N-donor co-ligands with Co(II) salt. In the biological function study, the treatment effect of compounds 1 and 2 on the Alzheimer's disease (AD) was evaluated and the detail mechanism was explored in this research. Firstly, the AD animal model was constructed, and the content of the Amyloid (Aβ) in the brain after compounds 1 and 2 treatment was detected. Then the protective activity of compounds 1 and 2 on neurons was evaluated after Aβ stimulation. Graphical Abstract: UF0001 Two new mixed-ligand coordination polymers have been synthesized. In the biological function study, the treatment effect of compounds 1 and 2 on the Alzheimer's disease (AD) was evaluated and the detail mechanism was explored in this research. Firstly, the AD animal model was constructed, and the content of the Amyloid (Aβ) in the brain after compounds 1 and 2 treatment was detected. Then the protective activity of compounds 1 and 2 on neurons was evaluated after Aβ stimulation.